Morphological, Genetic Diversity and Molecular Markers Study of Senna Species in Arid Regions - Njoud Abdulla Al-Ishaq (23753025) (2025)
The native Senna italica Mill (also known as Ishrig, Senna, and Senna mekki; ، مكي سنة سنة، عشرق ) is most prevalent in areas such as the Arabic Gulf countries. Senna is particularly important in traditional life in Qatar and the Gulf regions due to its biological activity and medicinal properties. The main goal of this study is to describe Senna spp. based on their physical features and genetic differences to understand how Senna species live and thrive in dry areas, especially in Qatar, by looking at Senna populations there, where local and non-local species coexist in tough and changing conditions. The main methods used in this project included closely examining the structure of Senna plants with scanning electron microscopy, extracting DNA to obtain genetic material, measuring the amount and quality of DNA with NanoDrop spectrophotometry, making copies of specific DNA parts using polymerase chain reaction (PCR), and sorting and studying DNA pieces by size with gel electrophoresis. The main results revealed significant differences in the morphology of native Senna italica in comparison to Senna occidentalis. There was a variation in stomatal numbers between the two species, where S. italica had more stomata than S. occidentalis, indicating a more efficient control of evaporation and gas exchange. For the molecular part, the DNA concentration for S. italica was 33.03 μg/ml, while that for S. occidentalis was 39.90 μg/ml. Primers 3 and 4 were used to amplify S. occidentalis in the PCR, while S. italica did not exhibit any amplification. This study revealed morphological and genetic differences between native Senna italica and non-native Senna occidentalis in Qatar, indicating adaptations for survival in arid environments. The differences in stomata number and DNA amplification patterns point to diverging evolutionary pathways and responses to severe conditions. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx